2016
DOI: 10.1124/dmd.115.068338
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Disposition of a Mixed Aldehyde Oxidase/Cytochrome P450 Substrate in Rats with Attenuated P450 Activity

Abstract: Marketed drugs cleared by aldehyde oxidase (AO) are few, with no known clinically relevant pharmacokinetic drug interactions associated with AO inhibition, whereas cytochrome P450 (P450) inhibition or induction mediates a number of clinical drug interactions. Little attention has been given to the consequences of coadministering a P450 inhibitor with a compound metabolized by both AO and P450. Upon discovering that VU0409106 (1) was metabolized by AO (to M1) and P450 enzymes (to M4-M6), we sought to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…(1-aminobenzotriazole) did not decrease carbazeran 4-oxidation, and 5) a panel of individual human recombinant cytochrome P450 enzymes (i.e., CYP1A2, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP3A4, and CYP3A5) did not catalyze carbazeran 4-oxidation to any appreciable extent. Consistent with our experimental results, it has been proposed that cytochrome P450 is not anticipated to catalyze carbazeran 4-oxidation when differences in the substrate specificity of AOX-1 and cytochrome P450 are the basis (Crouch et al, 2016;Lepri et al, 2017). In a previous in vivo pharmacokinetic study, it was reported that carbazeran is metabolized extensively in humans, with a calculated total body clearance that was twice that of the literature value of human hepatic blood flow (Kaye et al, 1984).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(1-aminobenzotriazole) did not decrease carbazeran 4-oxidation, and 5) a panel of individual human recombinant cytochrome P450 enzymes (i.e., CYP1A2, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP3A4, and CYP3A5) did not catalyze carbazeran 4-oxidation to any appreciable extent. Consistent with our experimental results, it has been proposed that cytochrome P450 is not anticipated to catalyze carbazeran 4-oxidation when differences in the substrate specificity of AOX-1 and cytochrome P450 are the basis (Crouch et al, 2016;Lepri et al, 2017). In a previous in vivo pharmacokinetic study, it was reported that carbazeran is metabolized extensively in humans, with a calculated total body clearance that was twice that of the literature value of human hepatic blood flow (Kaye et al, 1984).…”
Section: Discussionsupporting
confidence: 89%
“…Other experimental evidence of cytosolic contamination of our microsomal preparations include: 1) the functional activity of AOX-1, as assessed by another AOX-1-catalyzed reaction, O 6 -benzylguanine 8-oxidation, was detected in human liver microsomal incubations without the addition of NADPH, and this occurred in multiple pools of human liver microsomes obtained from multiple commercial suppliers; 2) an AOX-1 inhibitor (hydralazine) almost completely abolished the two AOX-1-mediated reactions (carbazeran 4-oxidation and O 6benzylguanine 8-oxidation) in human liver microsomal incubations; and 3) another well characterized cytosolic enzyme activity (DHEA sulfonation catalyzed by SULT2A1, SULT2B1, and SULT1E1) was also quantified in our pools of human liver microsomes. Previous studies detected AOX-1-catalyzed metabolites from carbazeran (Wilkinson et al, 2017), VU0409106 (Crouch et al, 2016), and SGX523 (Diamond et al, 2010) in human liver microsomes but did not quantify microsomal AOX-1 protein content and postulated the metabolite formation was the result of contamination of microsomes with cytosol (Crouch et al, 2016;Wilkinson et al, 2017). Overall, by using various experimental approaches to address the issue of cytosolic contamination of our panel of human liver microsomes, our results indicate that microsomal cytochrome P450 does not catalyze carbazeran 4-oxidation.…”
Section: Discussionmentioning
confidence: 52%
“…1) as a site for aldehyde oxidase (AO)-mediated metabolism. 11,18,19 Accurately predicting human pharmacokinetics with compounds that are substantially metabolized by AO can be more challenging due in part to its variable expression across preclinical species. 20 While compound 2 was not metabolized by AO, compound 1 ultimately had other characteristics that cumulatively yielded a superior profile compared to 2 .…”
mentioning
confidence: 99%
“…Second, compounds 32 and 52 showed that substitution of the triazole ring with a methyl group was unfavorable for mGlu 5 activity, resulting in 14 and 70-fold drops in potency, respectively. Finally, while we expected that the pyrimidin-5-yl ethers 33 and 53 would be prone to AO-mediated metabolism, 18,19 these compounds were also examined for the sake of comparison. As was the case with picolinamides 1 and 2 , both 33 and 53 were less potent than their respective 5-fluoropyridin-3-yl ether counterparts 31 and 51 ; however, the impact was more pronounced in the case of analog 33 .…”
mentioning
confidence: 99%
“…negative allosteric modulator of the metabotropic glutamate receptor subtype 5 (mGlu 5 NAM) (Felts et al, 2013), in which case in vitro oxidation of the pyrimidine ring to the principle 6-oxopyrimidine metabolite was mediated by AO in humans, monkeys, and rats (Morrison et al, 2012). In vitro and in vivo experiments in Sprague-Dawley rat using the XO inhibitor allopurinol indicated that a secondary oxidation, resulting in the formation of a 2,6-dioxopyrimidine metabolite, was mediated by XO (Morrison et al, 2012;Crouch et al, 2016). These metabolites were also produced in the cynomolgus monkey; however, experiments with allopurinol were not conducted.…”
Section: Introductionmentioning
confidence: 99%